Exchange Rate Pass-Through in an Emerging Market: The Case of the Czech Republic. Issue 11 (1st November 2016) - Hájek, Jan; Horváth, Roman
ABSTRACT: We examine exchange rate pass-through, or how domestic prices respond to exchange rate shocks, in the Czech Republic from 1998 to 2013 by employing vector autoregression models. Using the aggregate consumer price index and its subcomponents, we find that the peak response occurs between nine and thirteen months after the exchange rate shock. The average pass-through at the monetary policy horizon is approximately 20 percent at the aggregate level. Regarding the subcomponents, the degree of pass-through is greatest for food prices.